Tablet manufacturing method and granulated particles

JP7607621B2Active Publication Date: 2024-12-27LION CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022191745
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-30
Publication Date
2024-12-27
Estimated Expiration
2038-10-17

AI Technical Summary

Benefits of technology

【0007】 本発明の錠剤の製造方法によれば、良好な崩壊性を有し、摩損が抑制された錠剤が得られる。 本発明の造粒粒子群によれば、良好な崩壊性を有し、摩損が抑制された錠剤が得られる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607621000008
    Figure 0007607621000008
  • Figure 0007607621000009
    Figure 0007607621000009
  • Figure 0007607621000010
    Figure 0007607621000010
Patent Text Reader

Abstract

To provide a tablet manufacturing method that produces tablets having good disintegrability and suppressed abrasion, and to provide granulated particle groups. [Solution] A method for producing tablets, comprising a step of tableting a powder containing granulated particles comprising the following component (A) and component (B), wherein the total content of component (A) and component (B) is 30% by mass or more: Component (A): at least one selected from the group consisting of the following component (a1) and component (a2): Component (a1): at least one selected from the group consisting of acetaminophen and ethenzamide; Component (a2): at least one selected from the group consisting of allylisopropylacetylurea, caffeine, and anhydrous caffeine; Component (B): at least one selected from the group consisting of loxoprofen and a salt thereof;
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing tablets and granulated particles. [Background technology]

[0002] Tablets containing acetaminophen have good disintegration properties but are subject to friability. As a method for improving the wear resistance of tablets containing acetaminophen, a method has been proposed in which acetaminophen, etc. is granulated using a water-soluble polymer such as polyvinyl alcohol, and the resulting granules are compressed into tablets (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-210478 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, although the method of Patent Document 1 improves wear resistance, it significantly reduces the disintegration property of the tablet. An object of the present invention is to provide a method for producing tablets that have good disintegrability and are suppressed from wearing, and a granulated particle group. [Means for solving the problem]

[0005] As a result of intensive research, the present inventors have found that by granulating acetaminophen together with loxoprofen or a salt thereof to form a granulated particle group in which the total amount of these is 30% by mass or more, it is possible to suppress wear while maintaining disintegration properties. In addition, it has been found that for other drugs (ethenzamide, allylisopropylacetylurea, caffeine, anhydrous caffeine) that have the same wear problem as acetaminophen, wear can be suppressed by the same method while maintaining disintegration properties. The present invention is based on the above findings and has the following aspects.

[0006] [1] A method for producing a tablet, comprising a step of compressing a powder containing a granulated particle group comprising the following component (A) and component (B), wherein the total content of component (A) and component (B) is 30 mass% or more: Component (A): At least one selected from the group consisting of the following component (a1) and the following component (a2): (a1) Component: At least one selected from the group consisting of acetaminophen and ethenzamide. Component (a2): At least one selected from the group consisting of allylisopropylacetylurea, caffeine, and anhydrous caffeine. Component (B): At least one selected from the group consisting of loxoprofen and its salts. [2] The method for producing a tablet according to [1] above, further comprising a step of granulating at least the component (A) and the component (B) to obtain the granulated particle group prior to the step of compressing the powder into tablets. [3] The method for producing a tablet according to [2] above, wherein the step of obtaining the granulated particle group is carried out by a wet granulation method. [4] The method includes, before the step of obtaining the granulated particle group, at least a step of mixing the powdered (A) component and the powdered (B) component to obtain a powder mixture, The method for producing a tablet according to [2] or [3] above, wherein the step of obtaining the granulated particle group is a step of obtaining the granulated particle group by granulating the powder mixture. [5] The method for producing tablets according to [4] above, wherein the mixing time in the step of obtaining the powder mixture is 10 minutes or less. [6] The method for producing a tablet according to any one of [1] to [5] above, wherein the granulated particles have a water-soluble polymer content of 5% by mass or less. [7] The method for producing a tablet according to any one of the above [1] to [6], wherein the mass ratio represented by the component (A) / the component (B) is 0.1 to 12.5. [8] The method for producing a tablet according to any one of the above [1] to [7], wherein the granulated particles further contain the following component (C): Component (C): At least one selected from the group consisting of insoluble starch derivatives and insoluble cellulose derivatives. [9] The method for producing a tablet according to [8] above, wherein the mass ratio represented by the component (C) / (the component (A)+the component (B)) is 0.01 to 3.

[10] A group of granulated particles comprising the following component (A) and component (B), wherein the total content of component (A) and component (B) is 30 mass % or more: Component (A): At least one selected from the group consisting of the following component (a1) and the following component (a2): (a1) Component: At least one selected from the group consisting of acetaminophen and ethenzamide. Component (a2): At least one selected from the group consisting of allylisopropylacetylurea, caffeine, and anhydrous caffeine. Component (B): At least one selected from the group consisting of loxoprofen and its salts.

[11] The group of granulated particles according to

[10] above, wherein the content of the water-soluble polymer is 5% by mass or less.

[12] The group of granulated particles according to

[10] or

[11] above, wherein a mass ratio represented by the component (A) / the component (B) is 0.1 to 12.5.

[13] The group of granulated particles according to any one of

[10] to

[12] above, further comprising the following component (C): Component (C): At least one selected from the group consisting of insoluble starch derivatives and insoluble cellulose derivatives.

[14] The group of granulated particles according to

[13] above, wherein a mass ratio represented by the component (C) / (the component (A)+the component (B)) is 0.01 to 3. Effect of the Invention

[0007] According to the method for producing tablets of the present invention, tablets having good disintegrability and suppressed abrasion can be obtained. According to the granulated particles of the present invention, tablets having good disintegrability and suppressed abrasion can be obtained. [Brief description of the drawings]

[0008] [Figure 1]FIG. 1 is a side view showing an example of a tablet (standard R tablet or sugar-coated R tablet). [Diagram 2] FIG. 1 is a side view showing another example of a tablet (two-stage R tablet). [Diagram 3] FIG. 2 is a side view showing another example of a tablet (a circular, square flat tablet). [Figure 4] FIG. 2 is a side view showing another example of a tablet (a circular Sumimaru flat tablet). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] ≪Granulated particle group≫ The granulated particle group of the present invention (hereinafter also referred to as "particle group (X)") is a group of granulated particles (hereinafter also referred to as "particle (x)") containing component (A) and component (B), in which the total content of component (A) and component (B) is 30 mass% or more. It is preferable that the particles (x) further contain the component (C). The particles (x) may further contain components other than the components (A), (B) and (C) as necessary, provided that the effects of the present invention are not impaired.

[0010] <Component (A)> The component (A) is at least one selected from the group consisting of the component (a1) and the component (a2). When the particles (x) contain the component (A), the disintegration properties of the tablet are excellent. The component (a1) is at least one selected from the group consisting of acetaminophen and ethenzamide. Acetaminophen (N-(4-hydroxyphenyl)acetamide) and ethenzamide are antipyretic and analgesic ingredients listed in the Japanese Pharmacopoeia. Acetaminophen is also known as paracetamol. The component (a2) is at least one selected from the group consisting of allylisopropylacetylurea, caffeine, and anhydrous caffeine. Allylisopropylacetylurea is a sedative-hypnotic ingredient. Caffeine and anhydrous caffeine are central stimulants. The component (A) may use one type alone, or a suitable combination of two or more types.

[0011] <(B) component> The (B) component is at least one selected from the group consisting of loxoprofen and its salts. The particles (x) contain the (B) component, so that the tablet has excellent friability. Here, excellent friability means that the friability in a friability test is suppressed. The friability means both the friability measured after the production of the tablet (initial friability) and the friability measured after storage (friability after storage). The storage conditions for measuring the friability after storage may be the conditions shown in the examples described below, or equivalent conditions. The friability is measured by the tablet friability test method listed in the 17th revised Japanese Pharmacopoeia, or a friability test performed under equivalent conditions. The salt of loxoprofen is not particularly limited as long as it is a pharma- ceutical acceptable salt, and examples thereof include alkali metal salts such as sodium salt and potassium salt, and alkaline earth metal salts such as calcium salt. As the component (B), a salt of loxoprofen is preferred, and loxoprofen sodium is more preferred. The component (B) may exist in the form of a hydrate. An example of the hydrate is sodium loxoprofen dihydrate (corresponding to about 12% of the powdered drug in terms of water content).

[0012] <(C) component> Component (C) is at least one selected from the group consisting of insoluble starch derivatives and insoluble cellulose derivatives. Component (C) is used to further increase disintegrability and friability. Here, "insoluble" means that the solubility in water is "practically not soluble" as defined in the General Rules of the Japanese Pharmacopoeia, 17th Edition (the amount of solvent required to dissolve 1 g or 1 mL of solute is 10,000 mL or more at 20±5°C). Examples of insoluble starch derivatives include corn starch, wheat starch, potato starch, pregelatinized starch, partially pregelatinized starch, and the like. Examples of insoluble cellulose derivatives include crystalline cellulose, low-substituted hydroxypropyl cellulose, carmellose, carmellose calcium, carmellose sodium, croscarmellose sodium, ethyl cellulose, and the like. As component (C), from the viewpoint of maintaining good disintegrability or friability, corn starch, partially pregelatinized starch, crystalline cellulose, and low-substituted hydroxypropyl cellulose are preferred, and corn starch and low-substituted hydroxypropyl cellulose are more preferred. The component (C) may use one type alone, or a suitable combination of two or more types.

[0013] <Other ingredients> Other ingredients include the same as the optional ingredients of tablets described below.

[0014] <Content of each ingredient> In the particles (x), the total content of the (A) component and the (B) component is 30% by mass or more, preferably 40% by mass or more, more preferably 55% by mass or more, and even more preferably 80% by mass or more, based on the total mass of the particles (x). If the total content of the (A) component and the (B) component is equal to or more than the lower limit, the effect of suppressing wear of the tablet, particularly wear after storage, is excellent. The upper limit of the total content of the (A) component and the (B) component is not particularly limited and may be 100% by mass. Taking into consideration the preferred contents of the (C) component and other components, the upper limit can be appropriately set so that the total of all components is 100% by mass. In the present invention, the content of component (B) also includes the water that binds to loxoprofen.

[0015] In the particles (x), the mass ratio of the (A) component to the (B) component (hereinafter also referred to as "(A) / (B)") is preferably 0.1 to 12.5. When the (A) / (B) ratio is equal to or greater than the lower limit of the above range, the disintegration property is more excellent, and when the (A) / (B) ratio is equal to or less than the upper limit of the above range, the wear and tear of the tablets and the variation in the physical properties can be further suppressed. When the component (A) is the component (a1), the ratio (A) / (B) is more preferably from 0.5 to 12.5, further preferably from 1.0 to 10.0, and particularly preferably from 4.0 to 6.0. When the component (A) is the component (a2), the ratio (A) / (B) is more preferably from 0.1 to 5.0, further preferably from 0.5 to 3.0, and particularly preferably from 0.75 to 1.5.

[0016] When the particle (x) contains the (C) component, the mass ratio represented by (C) component / ((A) component+(B) component) (hereinafter also referred to as "(C) / (A+B)") is preferably 0.01 to 3, more preferably 0.01 to 0.42, even more preferably 0.02 to 0.3, and particularly preferably 0.07 to 0.2. When (C) / (A+B) is equal to or greater than the lower limit of the above range, the disintegration property and friability are more excellent. In addition, the effects of being able to suppress adhesion to equipment during tableting and improving the appearance stability after storage can also be obtained. When (C) / (A+B) is equal to or less than the upper limit of the above range, the total content of the (A) component and the (B) component can be sufficiently increased.

[0017] The content of the water-soluble polymer in the particles (x) is preferably 5% by mass or less, more preferably 2% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0% by mass, based on the total mass of the particles (x). That is, it is particularly preferable that the particles (x) do not contain a water-soluble polymer. The lower the content of the water-soluble polymer, the better the disintegration property. In the present invention, "water-soluble" means that the solubility in water at 20° C. is 1.3 g / 100 mL or more.

[0018] The average particle size of the particle group (X) is preferably 30 to 1500 μm, more preferably 50 to 700 μm. When the average particle size is equal to or more than the lower limit of the above range, adhesion to manufacturing equipment is suppressed, and when it is equal to or less than the upper limit of the above range, the uniformity of the powder is improved. The average particle size of the particle group (X) is a value measured by a laser diffraction / scattering particle size distribution measuring device (for example, "LS13320" manufactured by Beckman Coulter, Inc.).

[0019] The moisture content of the particle group (X) is preferably 0.1 to 4.0% by mass, more preferably 0.1 to 3.0% by mass, and even more preferably 0.1 to 2.0% by mass. When the moisture content of the particle group (X) is equal to or higher than the lower limit of the above range, wear and tear of the tablet can be further suppressed. When the moisture content of the particle group (X) is equal to or lower than the upper limit of the above range, the particle group (X) has excellent flowability, good filling properties in a die before tableting, and small weight deviation of the tablet. The moisture content of the particle group (X) is calculated from the loss on drying when the particle group (X) is heated for 10 minutes at 120° C. That is, when the mass (g) before heating is W1 and the mass (g) after heating is W2, it is calculated by the following formula. Moisture content (mass%) = (W1-W2) / W1×100

[0020] <Method of manufacturing granulated particles> The particle group (X) can be produced, for example, by a production method having a step of granulating at least the components (A) and (B) (a granulation step). The production method may, if necessary, have a step of mixing the powdered (A) component and the powdered (B) component (powder mixing step) before the granulation step. When the powder mixing step is included, the powder mixture obtained in the powder mixing step is granulated in the granulation step. Hereinafter, a detailed description will be given of a manufacturing method having a powder mixing step and a granulation step.

[0021] (Powder mixing process) In the powder mixing step, the powdered (A) component and the powdered (B) component are mixed to obtain a powder mixture. At this time, the powdered (C) component and other powdered components may be mixed together with the powdered (A) component and the powdered (B) component. Examples of other powdered components include excipients and disintegrants, which will be described later. The total amount of the powdered (A) component and the powdered (B) component relative to the total mass of the powder mixture corresponds to the total content of the (A) component and the (B) component relative to the total mass of the particles (x), and is 30 mass% or more.

[0022] Each component to be mixed in the powder mixing step may be manufactured by a known manufacturing method or may be commercially available. Each component may be used as a bulk powder as it is, may be crushed, or may be granulated. When the bulk powder is granulated, a known granulation method may be used as the granulation method.

[0023] The mixing method is not particularly limited, and may be any known powder mixing method. For example, each powder may be mixed using a device (mixer) generally used for powder mixing. Examples of the mixer include a fluidized bed granulator, an agitation granulator, a Bohle container mixer, a V-type mixer, a W-cone type mixer, and a ribbon mixer. Among these, a fluidized bed granulator and an agitation granulator are preferred from the viewpoints of efficient mixing of the powdered (A) component and the powdered (B) component, operability, and productivity. The order in which the powders are charged into the mixer is not particularly limited as long as it does not cause any problems in terms of production. The mixing conditions can be appropriately selected depending on the mixer used. For example, when mixing is performed using a fluidized bed granulator, the supply air temperature is 60 to 100°C and the supply air volume is 1.0 to 4.0 m 3 When mixing is performed using an agitator granulator, mixing can be performed at a chopper rotation speed of 500 to 3000 rpm and an agitator rotation speed of 100 to 500 rpm. The mixing time is preferably 10 minutes or less, more preferably 5 minutes or less, and even more preferably 3 minutes or less. If the mixing time is equal to or less than the upper limit, the disintegration property and friability of the tablet are more excellent. From the viewpoint of powder uniformity, the mixing time is preferably more than 0 seconds, more preferably 10 seconds or more, and even more preferably 20 seconds or more.

[0024] (granulation process) In the granulation step of this embodiment, the powder mixture obtained in the powder mixing step is granulated. Examples of the granulation method include a dry granulation method, a wet granulation method, etc. Examples of the wet granulation method include a fluidized bed granulation method, an agitation granulation method, a rolling granulation method, an extrusion granulation method, etc. As the granulation method, wet granulation is preferred from the viewpoint of manufacturability, and among them, fluidized bed granulation and stirring granulation are preferred from the viewpoints of efficient contact between component (A) and component (B), operability, and productivity. Granulation conditions can be appropriately selected depending on the granulation method. For example, when granulation is performed by a fluidized bed granulation method, the supply air temperature is 60 to 100°C, and the supply air volume is 1.0 to 4.0 m 3 When granulation is performed by the stirring granulation method, the chopper rotation speed can be set to 500 to 3000 rpm and the agitator rotation speed to 100 to 500 rpm.

[0025] Granulation may be carried out while spraying a liquid that does not cause problems in manufacturing, such as water, ethanol, etc. In general, in wet granulation, granulation is performed while spraying a binding liquid in which a binder such as a water-soluble polymer or a water-insoluble acrylic acid polymer is dispersed or dissolved in water. In the granulation step of this embodiment, granulation may be performed while spraying a binding liquid. In this case, the particles (x) constituting the obtained particle group (X) contain a binder. When the binder contains a water-soluble polymer, it is preferable that the binder content of the particles (x) is small in order to maintain good disintegration. Specifically, the amount of the binder solution sprayed is preferably an amount such that the content of the water-soluble polymer is 5% by mass or less relative to the total mass of the particles (x). The more preferable content of the water-soluble polymer is as described above.

[0026] After granulation, the resulting granules are dried, if necessary, for the purpose of adjusting the moisture content, etc. The drying method is not particularly limited, but shelf drying using a dryer such as a fluidized bed granulator or a box-type ventilation dryer is preferred. Drying conditions can be appropriately selected depending on the drying method. For example, when drying is performed using a fluidized bed granulator, the intake air temperature is 60 to 100°C, the drying time is 10 to 90 minutes, and the intake air volume is 1.0 to 4.0 m 3 When drying is performed using a box-type ventilation dryer, the drying temperature is 40 to 90°C and the drying time is 15 to 130 minutes.

[0027] Although the manufacturing method having the powder mixing step and the granulation step has been described above, the manufacturing method of the particle group (X) is not limited to this embodiment. For example, the particle group (X) may be produced by a production method having a granulation step but not having a powder mixing step. In this case, in the granulation step, the components to be granulated (component (A), component (B), component (C), etc.) may be contacted in a solid state such as powder, or in a state dissolved or dispersed in a liquid medium.

[0028] When the granulation step is performed without going through the powder mixing step, the order of feeding the (A) component and the (B) component into the granulator is not particularly limited as long as it does not cause any problems in production. For example, the (A) component may be fed and granulated, and then the (B) component may be fed into the granulator and further granulated, or the order of feeding the (A) component and the (B) component may be reversed. In terms of making the particles (x) more uniform and avoiding the process from becoming complicated, it is preferable to feed the (A) component and the (B) component into the granulator at the same time and perform granulation.

[0029] Tablets The tablet produced by the tablet production method of the present invention (hereinafter also referred to as "tablet (Y)") uses the particle group (X) and therefore contains components derived from the particle group (X). The component derived from the particle group (X) contains at least the component (A) and the component (B), and if necessary, the component (C) and other components. The component (A) may be only the component (a1), only the component (a2), or both the component (a1) and the component (a2). The tablet (Y) may further contain components not derived from the particle group (X) (hereinafter also referred to as "optional tablet components"), if necessary, within the scope of the present invention, the tablet properties, and storage stability.

[0030] Optional tablet ingredients include physiologically active ingredients, additives, etc. Examples of physiologically active ingredients include antipyretic and analgesic ingredients (e.g., piroxicam, meloxicam, ampiroxicam, cerocoxib, rofecoxib, tiaramide, sulpyrine, etc.), sedative and hypnotic ingredients (e.g., bromvalerylurea, etc.), antihistamine ingredients (e.g., isothipendyl hydrochloride, diphenylpyraline hydrochloride, diphenhydramine hydrochloride, diphenterol hydrochloride, triprolidine hydrochloride, tripelennamine hydrochloride, thonzylamine hydrochloride, fenethazine hydrochloride, methadylamine hydrochloride, dl-Chlorpheniramine maleate, d-Chlorpheniramine maleate, diphenyldisulfonate, diphenhydramine tannate, diphenylpyraline teoclate, mebhydroline napadisilate, promethazine methylene disalicylate, carbinoxamine maleate, dl-chlorpheniramine maleate, d-chlorpheniramine maleate, diphenterol phosphate, etc.), central stimulants (e.g., sodium benzoate, caffeine, etc.) ), antitussive and expectorant ingredients (e.g., codeine phosphate, dextromethorphan hydrobromide, dimemorphan phosphate, tipepidine hibenzate, methoxyphenamine hydrochloride, trimetoquinol hydrochloride, carbocysteine, acetylcysteine, ethylcysteine, dl-methylephedrine, bromhexine hydrochloride, serrapeptase, lysozyme chloride, ambroxol, theophylline, aminophylline), vitamin ingredients (e.g., vitamin B1 and its derivatives and their salts, vitamin B2 and its derivatives and their salts, vitamin C and its derivatives and their salts, hesperidin and its derivatives and their salts, etc.), antacids (e.g., dried aluminum hydroxide gel, magnesium aluminometasilicate, magnesium aluminosilicate, synthetic hydrotalcite, magnesium carbonate, magnesium oxide, magnesium silicate, sodium bicarbonate), etc. These physiologically active ingredients can be used alone or in appropriate combination of two or more. Among these physiologically active ingredients, at least one selected from the group consisting of dried aluminum hydroxide gel, magnesium aluminometasilicate, synthetic hydrotalcite, and magnesium oxide is preferred, since it has good disintegration and friability, can suppress odor changes after storage, and can provide a formulation with higher storage stability.

[0031] Examples of the additives include binders, excipients, disintegrants, flavors, lubricants, sweeteners, and acidulants. Examples of binders include crystalline cellulose, gelatin, powdered gum arabic, polyvinylpyrrolidone, pullulan, hypromellose, methylcellulose, hydroxypropylcellulose, hydroxymethylcellulose, hydroxypropylmethylcellulose, polyvinyl alcohol, polyethylene glycol, etc. Examples of excipients include lactose, mannitol, erythritol, xylitol, lactitol, trehalose, maltitol, corn starch, wheat starch, potato starch, dextrin, cyclodextrin, carboxymethylcellulose, carboxymethylcellulose calcium, L-cysteine, sodium hydrogen phosphate, calcium hydrogen phosphate, etc. Examples of disintegrants include low-substituted hydroxypropylcellulose, partially pregelatinized starch, carmellose, carmellose sodium, croscarmellose sodium, crospovidone, etc. Examples of lubricants include magnesium stearate, sodium stearyl fumarate, sucrose fatty acid ester, light anhydrous silicic acid, etc. Examples of flavorings include menthol, limonene, and plant essential oils (peppermint oil, mint oil, lychee oil, orange oil, lemon oil, etc.). Examples of sweeteners include saccharin, saccharin sodium, aspartame, stevia, dipotassium glycyrrhizinate, and acesulfame potassium. Examples of acidulants include citric acid, tartaric acid, malic acid, succinic acid, fumaric acid, lactic acid, and salts thereof.

[0032] The content of the component (a1) in the tablet (Y) is not particularly limited as long as it is within a range that does not cause problems in production. The content of the component (a1) per tablet of the tablet (Y) is preferably 30 to 500 mg, more preferably 50 to 300 mg, and even more preferably 100 to 230 mg. The proportion of the (a1) component to the total mass of the tablet (Y) is preferably 10 to 95 mass %, more preferably 35 to 85 mass %, and even more preferably 40 to 55 mass %. When the content of the (a1) component is equal to or greater than the lower limit of the above range, the disintegration property and the appearance stability after storage are superior. When the content of the (a1) component is equal to or less than the upper limit of the above range, the friability is superior. In addition, from the viewpoint of the tablet size, the tablet is easy to take.

[0033] The content of the component (a2) in the tablet (Y) is not particularly limited as long as it is within a range that does not cause problems in production. The content of the component (a2) per tablet of tablet (Y) is preferably 10 to 300 mg, more preferably 20 to 200 mg, and even more preferably 30 to 150 mg. The proportion of the (a2) component to the total mass of the tablet (Y) is preferably 5 to 75 mass %, more preferably 10 to 55 mass %, and even more preferably 15 to 40 mass %. When the content of the (a2) component is equal to or greater than the lower limit of the above range, the disintegration property and the appearance stability after storage are superior. When the content of the (a2) component is equal to or less than the upper limit of the above range, the friability is superior. In addition, from the viewpoint of the tablet size, the tablet is easy to take.

[0034] The content of the component (B) in the tablet (Y) is not particularly limited as long as it is within a range that does not cause problems in production. The content of the component (B) per tablet of tablet (Y) is preferably 5 to 170 mg, more preferably 10 mg to 113 mg, and even more preferably 20 mg to 85 mg, calculated as loxoprofen sodium dihydrate. The proportion of the component (B) relative to the total mass of the tablet (Y) is preferably 5 to 90 mass %, more preferably 5 to 60 mass %, and even more preferably 8 to 30 mass %. When the content of component (B) is equal to or greater than the lower limit of the above range, the friability is better, and when the content of component (B) is equal to or less than the upper limit of the above range, the appearance stability after storage is better.

[0035] The content of component (C) in tablet (Y) is not particularly limited as long as it is within a range that does not cause problems in production. The content of the component (C) per tablet of tablet (Y) is preferably 1 to 200 mg, more preferably 3 to 100 mg, and even more preferably 10 to 60 mg. The proportion of the component (C) relative to the total mass of the tablet (Y) is preferably 0.5 to 30 mass %, more preferably 1 to 20 mass %, and even more preferably 2 to 15 mass %. If the content of component (C) is equal to or greater than the lower limit of the above range, the disintegration and friability are superior. Furthermore, adhesion to manufacturing equipment and changes in appearance after storage can be suppressed. If the content of component (C) is equal to or less than the upper limit of the above range, the friability after storage is superior.

[0036] The content of the binder per tablet of tablet (Y) is preferably 0 to 30% by mass. The content of the excipient per tablet of tablet (Y) is preferably 0 to 40% by mass. The content of the disintegrant per tablet of tablet (Y) is preferably 0 to 20% by mass. The content of the flavor per tablet of tablet (Y) is preferably 0 to 5% by mass. The content of the lubricant per tablet of tablet (Y) is preferably 0 to 5% by mass. The content of the sweetener per tablet of tablet (Y) is preferably 0 to 5% by mass. The content of the acidulant per tablet of tablet (Y) is preferably 0 to 5% by mass.

[0037] The type of tablet (Y) is not particularly limited, and examples thereof include plain tablets, sugar-coated tablets, coated tablets, enteric-coated tablets, orally disintegrating tablets, chewable tablets, and effervescent tablets. The tablet (Y) may have a single layer structure (single layer tablet), a layered structure (layered tablet), or a dry-coated tablet. When the tablet (Y) is a layered tablet, at least one layer may be a layer using the particle group (X).

[0038] The dimensions of the tablet (Y) are not particularly limited, but from the viewpoints of ease of handling and swallowing of the tablet, the diameter φ of the tablet is preferably 5 to 14 mm, more preferably 6 to 13 mm, and even more preferably 7 to 12 mm. The mass of each tablet of the tablet (Y) is appropriately about 150 mg to 550 mg.

[0039] The shape of the tablet (Y) is not particularly limited in terms of the effects of the present invention, but from the viewpoint of ease of handling and swallowing of the tablet, a shape having a cylindrical portion and a bulging portion bulging up and down from the cylindrical portion is preferable. Examples of the tablet having the cylindrical portion and the bulging portion include R tablets (standard R tablets, sugar-coated R tablets, etc.), two-stage R tablets, Sumi square flat tablets, Sumi round flat tablets, etc. The bulging portions of these tablets may be asymmetrical from top to bottom, but are preferably symmetrical from top to bottom. Below, the shapes of standard R tablets or sugar-coated R tablets, two-tiered R tablets, circular square flat tablets, and circular round flat tablets are explained in detail using drawings.

[0040] As shown in FIG. 1, a standard R tablet or sugar-coated R tablet 100 is a biconvex tablet having a cylindrical portion 8, a first bulging portion 12, and a second bulging portion 22, and the radius of curvature R of the curved surface of each of the first bulging portion 12 and the second bulging portion 22 is constant regardless of the position on the bulging portion surface. The first bulge 12 bulges from near the periphery of one end face of the cylindrical portion 8 toward the center of the one end face. The second bulge 22 bulges from near the periphery of the other end face of the cylindrical portion 8 toward the center of the other end face. Here, "radius of curvature of the curve on the surface of first bulge portion 12" refers to the radius of the circle when the curve on the surface of first bulge portion 12 is considered to be part of a circle in a cross section cut perpendicular to the end face of cylindrical portion 8 so as to pass through zenith 12A. The "radius of curvature of the curve on the surface of the second bulge portion 22" refers to the radius of the circle when the curve on the surface of the second bulge portion 22 is considered to be part of a circle in a cross section cut perpendicular to the end face of the cylindrical portion 8 so as to pass through the zenith 22A. The zenith 12A of the first bulging portion 12 is the point located at the highest point relative to one end face, and the zenith 22A of the second bulging portion 22 is the point located at the lowest point relative to the other end face. The radius R of the first bulging portion 12 and the radius R of the second bulging portion 22 may be the same or different, and from the viewpoint of tablet strength, it is preferable that they are the same.

[0041] As shown in FIG. 2, the two-stage R tablet 200 has a cylindrical portion 8, a first bulging portion 12, and a second bulging portion 22. The radius of curvature R1 of the rising portion from the peripheral edge of each of the first bulging portion 12 and the second bulging portion 22 is different from the radius of curvature R2 of the zenith 12A, and it is a biconvex tablet with R1 < R2. The R1 of the first bulging portion 12 and the R1 of the second bulging portion 22 may be the same or different, and from the viewpoint of tablet strength, it is preferably the same. The R2 of the first bulging portion 12 and the R2 of the second bulging portion 22 may be the same or different, and from the viewpoint of tablet strength, it is preferably the same.

[0042] As shown in FIG. 3, the circular bevelled flat tablet 300 is a biconvex tablet having a cylindrical portion 8, a first bulging portion 12, and a second bulging portion 22. The first bulging portion 12 rises linearly from near the peripheral edge of one end face of the cylindrical portion 8 toward the center of the one end face at a predetermined rising angle θ, and any region including the zenith 12A becomes a plane. The second bulging portion 22 rises linearly from near the peripheral edge of the other end face of the cylindrical portion 8 toward the center of the other end face at a predetermined rising angle θ, and any region including the zenith 22A becomes a plane. The rising angle θ in the first bulging portion 12 and the rising angle θ in the second bulging portion 22 may be the same or different, and from the viewpoint of tablet strength, it is preferably the same.

[0043] As shown in FIG. 4, the circular bevelled round flat tablet 400 is a biconvex tablet having a cylindrical portion 8, a first bulging portion 12, and a second bulging portion 22. The first bulging portion 12 rises from near the peripheral edge of one end face of the cylindrical portion 8 toward the center of the one end face at a predetermined R, and any region including the zenith 12A becomes a plane. The second bulging portion 22 rises from near the peripheral edge of the other end face of the cylindrical portion 8 toward the center of the other end face at a predetermined R, and any region including the zenith 22A becomes a plane. The radius R of the first bulging portion 12 and the radius R of the second bulging portion 22 may be the same or different, and from the viewpoint of tablet strength, it is preferable that they are the same.

[0044] As shown in Figures 1 to 4, the standard R tablet or sugar-coated R tablet 100, the two-stage R tablet 200, the circular Sumi square flat tablet 300, and the circular Sumi round flat tablet 400 each have a horizontal surface (land portion 14) that is circular in plan view on the outer periphery of the first bulge portion 12, and a horizontal surface (land portion 24) that is circular in plan view on the outer periphery of the second bulge portion 22. The width of the land portion 14 is W. The "width of the land portion 14" refers to the distance from the periphery of the first bulge portion 12 to the periphery of the end face. The width of the land portion 24 may be the same as or different from W. From the viewpoint of tablet strength, the width of the land portion 24 is preferably the same as W.

[0045] From the viewpoint of ease of administration, the size of the tablet is preferably within the following range. Standard R lock: R=4.0~24.0mm, land width W=0.05~0.1mm. Sugar-coated R tablets: R=2.0~18.5mm, land width W=0.01~0.1mm. -Two-stage R lock...R1=1.2~8.0mm, R2=4.5~21.5mm, land width W=0.05~0.1mm. Circular Sumi round flat lock...R=0.7~5.0mm, land width W=0.05~0.1mm. Circular corner flat lock...Rise angle θ=25~35°, land width W=0.05~0.1mm.

[0046] For example, the tablet (Y) may not have a land portion, and the tablet periphery and the bulging rising portion may be in contact with each other. When the shape of the tablet (Y) is a circular corner flat tablet or a circular round flat tablet, any one of the areas including the apex of the first bulging portion and any one of the areas including the apex of the second bulging portion may not be flat. The shape of the tablet (Y) may not be circular in plan view, but may be an ellipse in plan view, a square in plan view, or a shape that is a combination of a circular shape and a square shape in plan view. The tablet (Y) may or may not have an engraving.

[0047] The shape of the tablet (Y) is not limited to the above-mentioned examples, but from the viewpoint of making it easier to obtain the effects of the present invention, R tablets, two-tiered R tablets, circular round flat tablets, or circular square flat tablets are preferred, R tablets, two-tiered R tablets, or circular round flat tablets are more preferred, and R tablets or two-tiered R tablets are even more preferred.

[0048] The moisture content of tablet (Y) is preferably 1 to 8%. When the moisture content of tablet (Y) is equal to or higher than the lower limit of the above range, the disintegration property is more excellent. When the moisture content of tablet (Y) is equal to or lower than the upper limit of the above range, the appearance stability after storage is good. The moisture content of tablet (Y) is calculated from the loss on drying when a crushed product of tablet (Y) is heated at 120° C. for 10 minutes. The method for calculating the moisture content is the same as that for the particle group (X). The moisture content of the tablet (Y) can be appropriately adjusted by the moisture content of the powder compressed during the production of the tablet (Y), the blending of optional components containing moisture, the drying conditions during the production process, and the like.

[0049] <Tablet manufacturing method> The method for producing a tablet of the present invention includes a step of compressing a powder containing the particle group (X) into tablets (tabletting step). Before the tableting step, the particle group (X) may be produced. The method for producing the particle group (X) is as described above.

[0050] (powder) The powder to be compressed in the tableting step (hereinafter also referred to as "powder for tableting") contains a particle group (X). The particle group (X) contained in the powder for tableting may be one type or two or more types. The powder for tableting may further contain other powders besides the particle group (X). When the powder for tableting is a mixture (hereinafter also referred to as "mixed powder") of multiple types of powder (powder containing two or more types of particle groups (X), powder containing one or more types of particle groups (X) and one or more types of other powder, etc.), a step of mixing multiple types of powder containing particle group (X) (powder for tableting preparation step) is carried out before the tableting step. In the powder for tableting preparation step, each powder can be mixed in the same manner as in the powder mixing step described above. Other powders include the powder of the optional tablet components described above. As the powder of the optional tablet components, the raw powder may be used as it is, or the granulated powder may be used. When the granulated powder is used, the granulation method may be a known granulation method. The content of the particle group (X) in the powder for tableting can be appropriately selected depending on the desired contents of the components (A) and (B) in the tablet (Y) to be produced.

[0051] (tableting process) The tableting method is not particularly limited, and may be any known tableting method, such as a method in which powder for tableting is tableted using a tableting machine having a mortar and a pestle. An example of a tablet press is a rotary tablet press (Libra 3L, manufactured by Kikusui Seisakusho Co., Ltd.). Tabletting conditions such as tableting pressure and rotation speed of the rotating disk are appropriately set. When the tablet (Y) is a layered tablet, the powder for tableting may be filled into the die first, or may be filled after the components constituting any layer.

[0052] After the tableting step, the tablets obtained in the tableting step may be subjected to a coating treatment with a coating agent, if necessary. It is preferable to select a coating agent that does not significantly impair disintegrability, and among these, water-soluble polymeric compounds and plasticizers are preferred. Examples of the water-soluble polymer compound include cellulose compounds such as hydroxypropyl cellulose, hydroxypropyl methyl cellulose, hydroxymethyl cellulose, and methyl cellulose, gum arabic, carboxyvinyl polymer, povidone, polyvinyl alcohol, and polyacrylic acid. Examples of the plasticizer include triethyl citrate, triacetin, and the like, which are listed in official compendia such as the Japanese Pharmacopoeia (Hirokawa Publishing) and Pharmaceutical Additives Standards (Yakuji Nipposha Co., Ltd.). These coating agents may be used alone or in combination of two or more. The coating treatment can be carried out by a known method.

[0053] In the tablet production method of the present invention described above, since tablets are produced by compressing powder containing the particle group (X), tablets having good disintegrability and suppressed abrasion can be obtained.

[0054] The tablet obtained by the tablet production method of the present invention can satisfy the following formula (1) and formula (2). t 2w <t 2w+4w (1) t 2w <t 0 (2) Here, t 2w indicates the disintegration time (seconds) of the tablet when the tablet is packed (sealed with aluminum foil) in a press-through package having a moisture permeability of 0.13 to 0.16 mg per pocket (40°C, 90% RH, 24 hours) and stored at 50°C, 75% RH for 2 weeks, and t 2w+4w indicates the disintegration time (seconds) of the tablet when the tablet is stored for an additional 4 weeks, and t 0 indicates the disintegration time (seconds) of the tablet before storage. The moisture permeability is a value determined by measurement in accordance with the moisture permeability test method of JIS Z 0208 moisture-proof packaging material.

[0055] Satisfying the above formulas (1) and (2) indicates that the disintegration time becomes shorter after about 2 weeks of storage under the above conditions than before storage, and then becomes longer. Tablets that exhibit such behavior have good disintegration properties and are not easily worn. t 2w It is preferable that the time is 5 seconds or more and less than 840 seconds (14 minutes). t 2w for t 0 The ratio is 105 to 500% (t 0 The time is preferably from 10 seconds to less than 900 seconds (15 minutes). t 2w for t 2w+4w The ratio is 105 to 1000% (t 2w+4w The time is preferably from 10 seconds to less than 1800 seconds (30 minutes). The disintegration time was determined by measuring the disintegration times of six tablets (using water as the disintegration test liquid) in accordance with the tablet disintegration test method listed in the Seventeenth Edition of the Japanese Pharmacopoeia, and averaging the measured values.

[0056] In this way, by using the particles (X), tablets having good disintegrability and suppressed abrasion can be obtained, and therefore the particles (X) are useful for tablets. However, the uses of the particle group (X) are not limited thereto. For example, the particle group (X) can be used in granules, capsules, powders, effervescent granules, etc. EXAMPLES

[0057] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following description.

[0058] <Raw materials used> Acetaminophen: Manufactured by Iwaki Pharmaceutical Co., Ltd., "Piretinol" Japanese Pharmacopoeia standard. Ethenzamide: Manufactured by Iwaki Pharmaceutical Co., Ltd., "Ethenzamide" Japanese Pharmacopoeia standard. Allylisopropylacetylurea: "Alipronal Congo" manufactured by Kongo Chemical Co., Ltd. Anhydrous caffeine: "Anhydrous caffeine 0.2 / 0.5" manufactured by Shiratori Pharmaceutical Co., Ltd. Isoprofen sodium dihydrate: Yamato Pharmaceutical Co., Ltd., Japanese Pharmacopoeia standard. Corn starch: "Official Matsutani Corn Starch" manufactured by Matsutani Chemical Industry Co., Ltd. Partially pregelatinized starch: "PCS" manufactured by Asahi Kasei Corporation. Low-substituted hydroxypropyl cellulose: "L-HPC LH-31" (registered trademark) manufactured by Shin-Etsu Chemical Co., Ltd. Crystalline cellulose: "UF-702" manufactured by Asahi Kasei Corporation. Crospovidone: "Kollidon (registered trademark) CL-SF" manufactured by BASF. Lactose granules: "Lactose G" manufactured by Freund Corporation. Magnesium stearate: "Magnesium stearate" manufactured by Taihei Chemical Industry Co., Ltd. Polyvinyl alcohol: "GOHSENOL EG04" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.

[0059] <Tableting conditions> Tablet press: Rotary tablet press Libra 3L (manufactured by Kikusui Seisakusho). Disc rotation speed: 20 rpm. Pestle: φ8.0mm (2-stage R) x 12 pieces, no engraving (cap height 0.1mm, R1=3.2, R2=9.5), or φ9.0mm (2-stage R) x 12 pieces, no engraving (cap height 0.1mm, R1=3.6, R2=10.5). Preload: 1kN (approx. 10MPa, approx. 100kg / cm 2 ). Main pressure: 11kN (approx. 110MPa, approx. 1100kg / cm 2 ).

[0060] <Method of measuring moisture content> The moisture content was calculated from the loss on drying when approximately 5 g of the sample was heated at 120°C for 10 minutes using an electronic moisture meter (MOISTURE BALANCE MOC-120H, manufactured by Shimadzu Corporation). In measuring the moisture content of the granulated particles, the granulated particles were used as they were as a sample. In measuring the moisture content of the tablet, the tablet was crushed in a mortar, and the crushed product was used as a sample.

[0061] <Evaluation method> (Evaluation of disintegration) The disintegration times of six tablets obtained were measured according to the tablet disintegration test method described in the 17th revised Japanese Pharmacopoeia (disintegration test liquid was water), and the average value was calculated. The disintegration property was evaluated from the average value obtained according to the following evaluation criteria. A score of 3 or more was considered to be acceptable. "Evaluation Criteria" 5: The average disintegration time is less than 5 minutes. 4: The average disintegration time is 5 minutes or more but less than 10 minutes. 3: The average disintegration time is 10 minutes or more but less than 15 minutes. 2: The average disintegration time is 15 minutes or more but less than 20 minutes. 1: Average disintegration time is 20 minutes or more.

[0062] (Wearability rating 1 (initial wearability rating)) The friability of the obtained tablets was measured three times in accordance with the tablet friability test method described in the 17th revised Japanese Pharmacopoeia, and the average value was calculated. The friability was evaluated from the average value based on the following evaluation criteria. A score of 2 or more was considered to be acceptable. "Evaluation Criteria" 4: Average wear rate is 0.3% or less. 3: Average wear and tear is greater than 0.3% and less than 0.6%. 2: The average wear level is greater than 0.6% and less than 1.0%. 1: Average wear and tear is greater than 1.0%.

[0063] (Wearability evaluation 2 (Wearability evaluation after storage)) The obtained tablets were placed in a pocket of a resin sheet (manufactured by Taisei Kako, "TAS-230") in which a pocket for storing tablets had been formed in advance, and aluminum foil was laminated on one side of the resin sheet to seal the opening of the pocket, obtaining a press-through package. This press-through package was stored at 50°C and 75% RH for 4 weeks. Thereafter, the tablets were removed from the press-through package, and the average value of the friability was calculated for the tablets in the same manner as in Evaluation 1 of the friability, to evaluate the friability. A score of 2 or more was considered to be acceptable.

[0064] <Examples 1, 3, 5, 7, 9, and 11 to 34, Production Examples 1 to 6, Comparative Examples 1 to 4> According to the blending ratio of the granulated particle group shown in Tables 1 to 7, the powder to be used for granulation was collected, and a total mass of 3 kg of the powder was placed in a fluidized bed granulator (manufactured by Freund Corporation, product name: FLO-5), and the supply air temperature was 80°C and the supply air volume was 2.0 m 3 The mixture was mixed for the mixing times shown in Tables 1 to 7 at 1 / min. Next, while spraying liquid into the fluidized bed granulator, the supply air temperature was set at 80°C and the supply air volume was set at 2.0 m 3Fluidized bed granulation was performed at 1000 mL / min. In Examples 1, 3, 5, 7, 9, and 11-34, Production Examples 1-6, and Comparative Examples 1, 3, and 4, water was sprayed as the liquid. The total amount of water sprayed was 1200 g relative to the total mass of the powder (3 kg). In Comparative Example 2, a binding liquid (5 mass% aqueous polyvinyl alcohol solution) was sprayed as the liquid. The total amount of binding liquid sprayed was an amount such that the mass of polyvinyl alcohol converted into solid content was the blending ratio shown in Table 7. Next, in the same fluidized bed granulator, the intake air temperature was 80°C and the intake air volume was 2.0 m 3 The granulated material was dried under conditions of 0.1 ml / min until the exhaust temperature reached 50° C., thereby obtaining granulated particle groups. The resulting granulated particles were mixed with the optional tablet ingredients shown in Tables 1 to 5, and the resulting mixed powder was compressed under the above-mentioned compression conditions to obtain tablets. A 9.0 mm mortar and punch were used for Examples 1, 3, 5, 7, 9, and 11 to 34 and Comparative Examples 3 and 4, and a 8.0 mm mortar and punch were used for Production Examples 1 to 6 and Comparative Examples 1 and 2.

[0065] <Examples 2, 4, 6, 8, and 10> According to the blending ratio of the granulated particle group shown in Table 1, the powder to be used for granulation was collected, and 3 kg of powder in total mass was placed in an agitation granulator (manufactured by EarthTechnica Co., Ltd., product name: High Speed ​​Mixer FS-10), 700 g of water was dropped, and agitation granulation was performed at a chopper rotation speed of 1500 rpm and an agitator rotation speed of 300 rpm. The obtained granulated material was placed in a fluidized bed granulator, and the inlet air temperature was 80°C and the inlet air volume was 2.0 m. 3 The granulated material was dried under conditions of 0.1 ml / min until the exhaust temperature reached 50° C., thereby obtaining granulated particle groups. Thereafter, the obtained granulated particle group and the optional tablet ingredients shown in Table 1 were mixed, and the obtained mixed powder was compressed using a φ9.0 mm mortar and pestle under the above-mentioned tableting conditions to obtain tablets.

[0066] The disintegration property and friability were evaluated for the tablets of Examples 1 to 34 and Comparative Examples 1 to 4. The results are shown in Tables 1 to 5 and 7.

[0067] [Table 1]

[0068] [Table 2]

[0069] [Table 3]

[0070] [Table 4]

[0071] [Table 5]

[0072] [Table 6]

[0073] [Table 7]

[0074] In Tables 1 to 7, the amount (mg) of each of the (A) component, (B) component, (C) component, optional component, and tablet optional component indicates the amount per tablet. A blank space indicates that the corresponding component is not blended. "%" is mass%.

[0075] The tablets of Examples 1 to 34 had good disintegrability. In addition, both the initial friability and the friability after storage were 2 points or more (1.0% or less). The tablet of Comparative Example 1, which did not use component (B), had an initial friability and a friability after storage of 1 point (more than 1.0%). The tablet of Comparative Example 2, in which a binder (polyvinyl alcohol) was used instead of component (B), had poor disintegration properties. The tablet of Comparative Example 3 in which component (B) was not mixed with the granulated particle group but was mixed as an optional tablet component had an initial friability and a friability after storage of 1 point (over 1.0%). The tablet of Comparative Example 4, in which the total content of components (A) and (B) in the granulated particle group was less than 30% by mass, had a friability of 1 point (more than 1.0%) after storage. [Explanation of symbols]

[0076] 100 Standard R tablets or sugar-coated R tablets 200 2-stage R lock 300 Circular Sumi flat lock 400 Circular Sumi round flat lock

Claims

1. The method includes a step of tableting a powder containing a granulated particle group containing the following component (A) and the following component (B): The granulated particles constituting the granulated particle group have a total content of the component (A) and the component (B) of 80% by mass or more relative to the total mass of the granulated particles, a content of a water-soluble polymer of 2% by mass or less relative to the total mass of the granulated particles, and a mass ratio of the component (A) / the component (B) of 0.1 to 1.

5. Component (A): At least one member selected from the group consisting of allylisopropylacetylurea, caffeine, and anhydrous caffeine. Component (B): At least one member selected from the group consisting of loxoprofen and its salts.

2. The method for producing tablets according to claim 1, further comprising a step of granulating at least the component (A) and the component (B) to obtain the granulated particle group prior to the step of compressing the powder into tablets.

3. The method for producing tablets according to claim 2 , wherein the step of obtaining the granulated particle group is carried out by a wet granulation method.

4. The method includes, before the step of obtaining the granulated particle group, at least a step of mixing the powder-form (A) component and the powder-form (B) component to obtain a powder mixture, The method for producing a tablet according to claim 2 or 3, wherein the step of obtaining the granulated particle group is a step of obtaining the granulated particle group by granulating the powder mixture.

5. The method for producing tablets according to claim 4, wherein the mixing time in the step of obtaining the powder mixture is 10 minutes or less.

6. The method for producing a tablet according to any one of claims 1 to 5, wherein the granulated particles further contain the following component (C): Component (C): The solubility in water is 10,000 mL or more (20±5°C) in terms of the amount of solvent required to dissolve 1 g or 1 mL of solute, and is at least one selected from the group consisting of corn starch, wheat starch, potato starch, partially pregelatinized starch, crystalline cellulose, low-substituted hydroxypropyl cellulose, carmellose, carmellose calcium, croscarmellose sodium, and ethyl cellulose.

7. The method for producing a tablet according to claim 6, wherein the mass ratio represented by the (C) component / (the (A) component+the (B) component) is 0.01 to 3.

8. The method for producing a tablet according to any one of claims 1 to 7, wherein the moisture content of the granulated particle group is 0.1 to 2.0% by mass.

9. A granulated particle group comprising the following component (A) and the following component (B): The granulated particles constituting the granulated particle group have a total content of the component (A) and the component (B) of 80% by mass or more relative to the total mass of the granulated particles, a content of a water-soluble polymer of 2% by mass or less relative to the total mass of the granulated particles, and a mass ratio of the component (A) / the component (B) of 0.1 to 1.

5. Component (A): At least one member selected from the group consisting of allylisopropylacetylurea, caffeine, and anhydrous caffeine. Component (B): At least one member selected from the group consisting of loxoprofen and its salts.

10. The granulated particle group according to claim 9, further comprising the following component (C): Component (C): The solubility in water is 10,000 mL or more (20±5°C) in terms of the amount of solvent required to dissolve 1 g or 1 mL of solute, and is at least one selected from the group consisting of corn starch, wheat starch, potato starch, partially pregelatinized starch, crystalline cellulose, low-substituted hydroxypropyl cellulose, carmellose, carmellose calcium, croscarmellose sodium, and ethyl cellulose.

11. The granulated particle group according to claim 10, wherein the mass ratio represented by the (C) component / (the (A) component+the (B) component) is 0.01 to 3.

12. The granulated particle group according to any one of claims 9 to 11, having a moisture content of 0.1 to 2.0 mass%.

Citation Information

Patent Citations

  • Medicinal preparation containing loxoprofen

    JP1999139971A

  • Solid internal medicine composition

    JP2010270019A

  • Medicinal preparation

    JP2011046692A

  • Pharmaceutical composition including loxoprofen

    JP2013133299A

  • Antipyretic analgesic composition

    JP2013136566A